Promiscuously Partisan? Public Service Impartiality and Responsiveness in Westminster Systems. Issue 4 (15th July 2016) - Grube, Dennis C.; Howard, Cosmo
Abstract : Public servants in Westminster countries are being drawn into the limelight by demands from their political masters that they publicly defend policies. Critics suggest these conditions undermine the capacity and willingness of senior public servants to manage the enduring Westminster tension between serving elected governments and remaining nonpartisan. Interviews with senior officials from Australia, Canada, and the United Kingdom challenge this pessimistic view, showing that officials consistently stress the importance of not "crossing the line" when dealing with their elected masters. Two exploratory case studies are presented—one of an Australian ministerial department (Treasury) and another of a Canadian quasi‐autonomous agency (Statistics Canada)—in which public servants faced pressure to defend controversial government policies. These cases show how contemporary public servants actively interpret, establish, and defend the line between appropriate responsiveness and inappropriate partisanship in Westminster systems.